Surgical Management of Adenocarcinoma of the Pancreatic Uncinate Process in a Cancer Hospital in Egypt - Sameh Roshdy; Osama Hussein; Ahmed Abdallah; Khaled Abdel-Wahab; Ahmed Senbel (Clinical Medicine Insights: Gastroenterology, 2015)
Introduction Pancreatic carcinoma affecting the uncinate process is a challenging surgical condition. Several considerations affect the management plan, including the need for vascular resection and the ability to achieve a clear margin. Methods The data of 19 patients who had curative resection for pancreatic adenocarcinoma of the uncinate process were reviewed. Operative mortality and morbidity, and disease-free survival (DFS) were calculated. Results The study population included 13 male and 6 female patients with a mean age of 55 years. Nine patients (47.4%) had stage I disease, seven patients (36.8%) had stage II disease, and three patients (15.8%) had stage III disease. A total of 12 patients had Whipple procedure and 7 patients had total pancreatectomy. In total, there were 9 R0 and 10 R1 resections. Operative mortality rate was 10.5% (2/19), postoperative leakage rate was 21.1% (4/19), and wound sepsis rate was 21.1%. Median DFS was 19.2 months. Survival was superior in the Whipple procedure group than in the total pancreatectomy group (median survival 19 months vs 4 months, respectively). Vascular resection and retroperitoneal safety margin status did not affect disease relapse. Conclusion Non-metastatic pancreatic adenocarcinoma of the uncinate process should be offered R0 or R1 resection whenever technically feasible.